Pengaruh Kualitas Pelayanan dan Sistem Informasi Akuntansi terhadap Kepercayaan di e-commerce yang dimoderasi oleh Kepuasan - Rachma Widyani; Ajeng Wijayanti (STKIP PGRI SITUBONDO, 2022)
This research aims to recommend the effect of service quality and accounting information systems on trust and to test the effect of moderation of satisfaction on the effect of service quality and accounting information systems on trust. The research method used is quantitative with data collection techniques through the distribution of questionnaires and the number of samples obtained by 200 respondents . the population in this study, namely MSMEs who have used e-commerce in the JABODETABEK region. The data processing method in this study uses Smart software PLS used in testing validity tests and reliability tests as well as in hypothesis testing. From the results of the hypothesis test it proves that there is a positive and significant influence of the quality of service on trust, the existence of a positive and significant influence of the accounting information system on trust, there is a positive and significant influence on satisfaction with trust, the absence of a positive and significant influence of moderating satisfaction on the influence of service quality on trust, there is a positive and significant influence of moderating satisfaction on the influence of accounting information systems.